Venous Thrombosis during Pregnancy: Leg and Trimester of Presentation - Ginsberg, J S; Brill-Edwards, P; Burrows, R F; Bona, R; Prandoni, P; Büller, H R; Lensing, A (Thrombosis and Haemostasis, 1992)
In order to determine the relative frequencies of left and right leg venous thrombosis during pregnancy and the frequencies of venous thrombosis during the three trimesters, a cohort study of 60 consecutive patients with a first episode of venous thrombosis during pregnancy was performed. Fifty-eight women had isolated left leg thrombosis, two patients had bilateral venous thrombosis and no patient had isolated right leg venous thrombosis. Thirteen patients had venous thrombosis during the first trimester (21.7%), 28 during the second trimester (46.7%) and 19 during the third trimester (31.7%). These findings indicate that patients with symptoms in the right leg rarely have venous thrombosis. Because leg pain and swelling occur most frequently during the third trimester but venous thrombosis is relatively equally distributed during all three trimesters, patients presenting earlier during pregnancy are more likely to have venous thrombosis than patients presenting later during pregnancy.